Lecture 3 (Indefinite Integral)

Download as pdf or txt
Download as pdf or txt
You are on page 1of 16

Integration

• Introduction
Lecture No. 3:
• Formulas for indefinite
Integration integral
• Trigonometric function
integration
• Integration by substitutions
Anti – derivatives (Indefinite Integrals)
• By Definition:

𝑑
If 𝑓((𝑥)) = 𝑓′(𝑥) ⇒ ∫ 𝑓′(𝑥)𝑑𝑥 = 𝑓(𝑥) + 𝑐 where 𝑐 is any arbitrary constant
𝑑𝑥

𝑑
• For example, we know that 𝑥 2 = 2𝑥 ⇒ ∫ 2𝑥𝑑𝑥 = 𝑥 2 + 𝑐
𝑑𝑥

• The integration constant is an essential part of every indefinite integral and


this is because the derivative of any constant is zero
The basic characteristics for Indefinite
integration
1- Indefinite integration only distributed on sum and difference of functions within
the integrand.

2- Indefinite integration cannot be distributed on multiplication and division.

3- In indefinite integration, the constants can be taken outside integration sign.


Original
Integral function Illustrative examples
𝐼 = ∫ 𝑓 ′ (𝑥)𝑑𝑥
∫ 𝑑𝑥 = ∫ 1 ⋅ 𝑑𝑥 𝐼 =𝑥+𝑐 𝐼 = ∫ 𝑑𝑥 = 𝑥 + 𝑐
∫ 𝑏 𝑑𝑥 𝐼 = 𝑏𝑥 + 𝑐 𝐼 = ∫ 3𝑑𝑥 = 3𝑥 + 𝑐
𝑥2
𝐼 = න 𝑥𝑑𝑥 = +𝑐
𝑥2 2
∫ 𝑏𝑥 𝑑𝑥 𝐼 =𝑏 +𝑐
2 7 7 𝑥2 7𝑥 2
𝐼=∫ 𝑥𝑑𝑥 = +𝑐 = +𝑐
2 2 2 4
𝑥3
𝐼 = න 𝑥 2 𝑑𝑥 = +𝑐
𝑥 𝑛+1 3
∫ 𝑥 𝑛 𝑑𝑥, 𝑛 ≠ −1 𝐼= +𝑐
𝑛+1 −5𝑥 5
𝐼=∫ − 5𝑥 4 𝑑𝑥 = +𝑐 =
5
Original
Integral function Illustrative examples
𝐼 = ∫ 𝑓 ′ (𝑥)𝑑𝑥
1 𝑥 −3+1
𝐼 = න 3 𝑑𝑥 = න 𝑥 −3 𝑑𝑥 = +𝑐
𝑥 −3 + 1
𝑑𝑥 𝑥 −𝑛+1
∫ 𝑛 = ∫ 𝑥 −𝑛 𝑑𝑥, 𝑛 ≠ 1 𝐼= +𝑐
𝑥 −𝑛 + 1 4
𝐼 = න 2 𝑑𝑥 = න 4𝑥 −2 𝑑𝑥 = −4𝑥 −1 + 𝐶
𝑥

1
𝑏 - 𝐼 = ∫ 𝑑𝑥 = ln 𝑥 + 𝑐
න 𝑑𝑥 𝐼 = 𝑏 ln 𝑥 + 𝑐 𝑥
𝑥 4
-𝐼=∫ 𝑑𝑥 = 4ln 𝑥 + 𝐶
𝑥
1
𝐼 = න 3 𝑥𝑑𝑥 = න 3𝑥 2 𝑑𝑥
𝑚
න𝒃 𝑥 𝑛 𝑑𝑥 𝑛
𝑥 𝑛+1 1 3
𝑛
𝐼=𝑏𝑛 +𝑐 𝑥 2+1 𝑥2
+1 𝐼=3 +𝑐 =3 +𝑐
=න 𝑏𝑥 𝑚 𝑑𝑥 𝑚 1 3/2
+1
2
Original
Integral function Illustrative examples
𝐼 = ∫ 𝑓 ′ (𝑥)𝑑𝑥

𝑏 1 2
−5
න𝑚 𝑑𝑥 𝐼=න 5 𝑑𝑥 = න 𝑥 𝑑𝑥
𝑥𝑛
𝑛
−𝑚+1 𝑥2
𝑥
𝐼=𝑏 𝑛 +𝑐 2 3
𝑛
−𝑚 − +1 𝑥 5+1 𝑥5
= න 𝑏𝑥 𝑑𝑥 𝑚 𝐼= +𝐶 = +𝐶
2 3/5
− +1
5
3 +3𝑥−4
𝐼 = න 3𝑥 2 + 3 𝑒 𝑥 𝑑𝑥

𝑥 3 +3𝑥−4
𝐼= 𝑒 +𝑐
𝐼 = ∫ 𝑒 𝑓(𝑥) 𝑓 ′ (𝑥)𝑑𝑥 𝐼 = 𝑒 𝑓(𝑥) + 𝑐
3 +3𝑥 2 +5
𝐼 = න 12𝑥 2 + 6𝑥 𝑒 4𝑥 𝑑𝑥

4𝑥 3 +3𝑥 2 +5
𝐼= 𝑒 +𝑐
Original
Integral function Illustrative examples
𝐼 = ∫ 𝑓 ′ (𝑥)𝑑𝑥
4−𝑥 5
5 𝑎
𝑎 𝑓(𝑥) 𝐼 = න −5𝑥 4 𝑎4−𝑥 𝑑𝑥 = +𝑐
𝐼= ∫ 𝑎 𝑓(𝑥) 𝑓 ′ (𝑥)𝑑𝑥 𝐼= +𝑐 ln 𝑎
ln 𝑎

1
1 ′ −𝐼 = න 3𝑥 2 + 4 𝑑𝑥 = ln 𝑥 3 + 4𝑥 + 𝑐
𝐼=න 𝑓 (𝑥)𝑑𝑥 𝑥 3 + 4𝑥
𝑓(𝑥) 𝐼 = ln 𝑓(𝑥) + 𝑐
1
−𝐼 = ∫ 𝑑𝑥 = ln(𝑥 + 14) +c
(𝑥+14)

n+1 cos 4𝑥
n ′
𝐼=න 𝑓 𝑥 𝑓 (𝑥)𝑑𝑥 𝑓 𝑥 − 𝐼 = න cos 3 𝑥 (−𝑠𝑖𝑛𝑥)𝑑𝑥 = +𝑐
𝐼= +𝑐 4
𝑛+1
Integral Original function

∫ sin𝑥𝑑𝑥 𝐼 = −cos𝑥 + 𝑐

∫ cos𝑥𝑑𝑥 𝐼 = sin𝑥 + 𝑐

∫ sec 2 𝑥𝑑𝑥 𝐼 = tan𝑥 + 𝑐

∫ csc 2 𝑥𝑑𝑥 𝐼 = −cot𝑥 + 𝑐

∫ sec𝑥tan𝑥𝑑𝑥 𝐼 = sec𝑥 + 𝑐

∫ csc𝑥cot𝑥𝑑𝑥 𝐼 = −csc𝑥. +𝑐

∫ sec𝑥𝑑𝑥 𝐼 = ln(sec𝑥 + tan𝑥) + 𝑐

∫ csc𝑥𝑑𝑥 𝐼 = −ln(csc𝑥 + cot𝑥) + 𝑐

∫ tan𝑥𝑑𝑥 𝐼 = ln (sec𝑥) + 𝑐

∫ 𝐜𝐨𝐭𝑥 𝑑𝑥 𝐼 = ln (sin 𝑥) + 𝑐
Trigonometric Functions with angle 𝑓(𝑥)
• When dealing with the integration of Trigonometric or hyperbolic function that
has an angle 𝑓(𝑥) , The derivative of the inner function 𝑓’(𝑥) must be present to
apply the standard integration rules.
• ∫ cos(𝑓(𝑥))𝑓 ′ (𝑥)𝑑𝑥 = sin(𝑓(𝑥)) + 𝑐
• Examples:-
• 𝐼 = ∫ 2cos 2𝑥 𝑑𝑥 ⇒
𝐼 = sin(2𝑥) + 𝑐
• 𝐼 = ∫ sec 2 2𝑥 2 − 3𝑥 + 2 4𝑥 − 3 𝑑𝑥 ⇒
𝐼 = tan 2𝑥 2 − 3𝑥 + 2 + 𝑐
𝒙𝟑/𝟐 +𝒙+𝟑𝒙𝟏/𝟐 +𝟒
• Example 1: ∫ 𝒅𝒙
𝒙𝟏/𝟐

1/2 4 𝑥2 𝑥 3/2
• =∫ 𝑥+𝑥 +3+ 𝑑𝑥 = + + 3𝑥 + 8 𝑥 + 𝑐
𝑥 2 3/2

𝒙𝟑
• Example 2: ∫ 𝒅𝒙
𝒙𝟒 +𝟐
1 4𝑥 3 1 1
•= ∫ 𝑑𝑥 = × 2 𝑥 4 + 2 + 𝑐 = 𝑥4 + 2 + 𝑐
4 𝑥 4 +2 4 2

𝟐 𝟐
• Example 3: ∫ 𝒙 + 𝟏 𝒅𝒙
𝑥5 𝑥3
• =∫ 𝑥4 + 2𝑥 2 + 1𝑑𝑥 = +2 +𝑥+𝑐
5 3
𝟏+𝒕𝒂𝒏𝟐 𝒙 𝐭𝐚𝐧 𝒙
• Example 4: ∫ 𝒅𝒙
𝐬𝐞𝐜 𝒙
sec2 𝑥tan 𝑥
• =∫ 𝑑𝑥 = ∫ sec 𝑥tan 𝑥𝑑𝑥 = sec 𝑥 + 𝑐
sec 𝑥
𝟏
• Example 5: ∫ 𝒅𝒙
𝒔𝒊𝒏𝟐 𝒙𝐬𝐞𝐜 𝒙
cos 𝑥 1 cos 𝑥
• =∫ 𝑑𝑥 =∫ × 𝑑𝑥 = ∫ csc 𝑥cot 𝑥𝑑𝑥 = −csc 𝑥 + 𝑐
sin2 𝑥 sin 𝑥 sin 𝑥
𝒙𝟒
• Example 6: ∫ 𝒙𝟓 +𝟐 𝒅𝒙
1 5𝑥 4 1
•= ∫ 𝑥 5 +2 𝑑𝑥 = ln 𝑥 5 + 2 + 𝑐
5 5
𝟑
• Example 7: ∫ 𝒙𝟐 + 𝟏 𝒅𝒙
6 4 2 𝑥7 𝑥5
• = ∫ 𝑥 + 3𝑥 + 3𝑥 + 1𝑑𝑥 = +3 + 𝑥3 + 𝑥 + 𝑐
7 5
(𝟏+𝐬𝐢𝐧 𝒙)
• Example 8: ∫ 𝒅𝒙
𝐜𝐨𝐬 𝒙

• = ∫ sec 𝑥 + tan 𝑥𝑑𝑥 = ln |sec 𝑥 + tan 𝑥| + ln |sec 𝑥| + 𝑐


• Example 9: ∫ 𝒔𝒊𝒏𝟑 𝒆𝒙 𝐜𝐨𝐬 𝒆𝒙 𝒆𝒙 𝒅𝒙
sin4 𝑒 𝑥
• =∫ sin 𝑒 𝑥 3 cos 𝑒 𝑥 𝑒 𝑥 𝑑𝑥 = +𝑐
4

• Example 10: ∫ 𝒙𝐬𝐢𝐧 𝒙𝟑 𝒅𝒙


2 3 2
• = ∫ 𝑥 1/2 sin 𝑥 3/2 𝑑𝑥 = − cos 𝑥 3/2 + 𝑐
3 2 3
𝒅𝒙
• Example 11: ∫ 𝒙𝐥𝐧 𝒙
𝟏/𝒙
• =∫ 𝒅𝒙 = ln |ln 𝑥| + 𝑐
𝐥𝐧 𝒙
𝐥𝐧 𝒙
• Example 12: ∫ 𝒅𝒙
𝒙
1
ln 𝑥 1 1 1 ln2 𝑥 1 2
• =∫ 2
𝑑𝑥 = ∫ ln 𝑥 𝑑𝑥 = = ln 𝑥 +𝑐
𝑥 2 𝑥 2 2 4
𝒅𝒙
• Example 13: ∫
𝒙 𝒙+𝟏
1
2 𝑥
• = 2∫ 𝑑𝑥 = 2 × 2 𝑥+1+𝑐
𝑥+1
𝒅𝒙
• Example 14: ∫
𝒙 𝒙+𝟏

1/ 𝑥 1/2 𝑥
• =∫ 𝑑𝑥 = 2∫ 𝑑𝑥 = 2ln( 𝑥 + 1) + 𝑐
( 𝑥+1) ( 𝑥+1)
𝒅𝒙
• Example 15: ∫
𝟑𝒙+𝟏− 𝟑𝒙−𝟏
1 ( 3𝑥+1+ 3𝑥−1)
=∫ × 𝑑𝑥
( 3𝑥+1− 3𝑥−1) ( 3𝑥+1+ 3𝑥−1)
( 3𝑥+1+ 3𝑥−1) 1 1 (3𝑥+1)3/2 (3𝑥−1)3/2
• =∫ 𝑑𝑥 = ∫ ( 3𝑥 + 1 + 3𝑥 − 1)𝑑𝑥 = + +𝑐
(3𝑥+1)−(3𝑥−1) 2 2 (3/2)(3) (3/2)(3)
1
= (3𝑥 + 1)3/2 + (3𝑥 − 1)3/2 + 𝑐
9
Integration by substitution
• Integration by substitution is a technique used to simplify the process of
integrating complex functions
• It involves substituting a part of the integrand with a new variable to make the
integral easier to solve.
• Example ∫ 𝟐𝒙 𝒄𝒐𝒔 𝒙𝟐 𝒅𝒙
2 𝑑𝑢 𝑑𝑢
Let 𝑢 = 𝑥 . Then, = 2𝑥 implies that 𝑑𝑢 = 2𝑥𝑑𝑥 or 𝑑𝑥 = .
𝑑𝑥 2𝑥

• ∫(2𝑥)cos 𝑥 2 𝑑𝑥 = ∫ cos(𝑢)𝑑𝑢
• ∫ cos(𝑢)𝑑𝑢 = sin(𝑢) + 𝐶
• Back Substitute 𝐬𝐢𝐧(𝒙𝟐 ) + 𝑪
𝒙𝟑 𝒅𝒙
• Example ∫
𝒙𝟐 +𝟐

Let 𝑥 2 + 2 = 𝑢 ⇒ 𝑥 2 + 2 = 𝑢2 ⇒ 2𝑥𝑑𝑥 = 2𝑢𝑑𝑢


𝑥 3 𝑑𝑥 𝑥 2 𝑥𝑑𝑥
න =න =
𝑥2 + 2 𝑥2 + 2

𝑢2 − 2 𝑢𝑑𝑢 𝑢 3
න = න 𝑢2 − 2𝑑𝑢 = − 2𝑢 + 𝑐
𝑢 3

𝑥2 + 2 3/2
= − 2 𝑥2 + 2 1/2 +𝑐
3
𝒙𝟐
Example ∫ 𝟒 𝒅𝒙
𝒙+𝟏

Set 𝑢4 = 𝑥 + 1 ⇒ 𝑥 = 𝑢4 − 1 → d𝑥 = 4𝑢3 d𝑢
u4 − 1 2
න 4𝑢3 𝑑𝑢
𝑢

𝑢8 − 2𝑢4 + 1
=න ⋅ 4𝑢3 𝑑𝑢 = 4 න 𝑢10 − 2𝑢6 + 𝑢2 𝑑𝑢
𝑢

4 11 8 7 4 3
= 𝑢 − 𝑢 + 𝑢 +𝑐
11 7 3
4 11/4
8 4
= (𝑥 + 1) − (𝑥 + 1) + (𝑥 + 1)3/4 +𝑐
7/4
11 7 3

You might also like